The Parasite specifity of cytotoxic T cells from cattle immunized with Buffalo and cattle- derived Theileria parva parasites. - Kariuki, T.M. (University of Nairobi, 1989)
Immunity to East Coast fever, a parasitic disease of cattle, is partially attributable to a cell-mediated immune response directed at cells infected with the schizont stage of the parasite. This response is in the form of cytotoxic T cells which can be measured in vitro after stimulating peripheral blood mononuclear cells (PBM) from immune animals (but not from naive animals) with their own autologous Theileria parva~infected cells. This study evaluated the parasite strain specificity of cytotoxic cells generated in cattle immunized with one of 5 different stocks of buffalo-derived T.parva lawrencei parasites or with cattle-derived T.p.parva (Uganda) or T.p.bovis (Boleni) parasite stocks. The objective was to determine whether any of these stocks was able to generate non-strain restricted immune T cells, that would recognize and subsequently lyse lymphocytes infected with different strains of T.parva parasites. Ultimately such information would be useful in identifying an antigen on the surface of schizont-infected cells which is common among cell lines infected with many different strains or stocks of T.parva parasites, and which could potentially form the basis of a recombinant subunit vaccine against East coast fever. To do this a group of 7 embryo transfer cattle, sharing the same parents and matched for at least one bovine lymphocyte antigen (BoLA) A-locus specificity, were immunized by infection and treatment. Cell lines to be used as target cells in in vitro cytotoxicity assays were generated by infection of PBM with the 5 buffalo parasite stocks as well as with the cattle-derived parasite stocks T.p.parva (Uganda), (Muguga), (Marikebuni), (Mariakani), and T.p.bovis (Boleni). PBM from the 7 cattle were evaluated in cytotoxicity assays following repeated stimulation in vitro with autologous or major histocompatibility complex (MHC)-matched cells infected with the same parasite stock as was used for immunization of the animal. It was possible to generate cytotoxic cells from all 7 cattle which were specific for MHC-matched cells infected with T.parva parasites. Testing for MHC restriction specificity using a panel of lymphocytes of different MHC backgrounds but infected with a single T.parva parasite stock were carried out and the results indicated bias in response towards one of the 2 BoLA A-locus class 1 specificities of the donor animals. In addition, limiting dilution assays for the estimation of the frequency of precursors of cytotoxic T cells with various parasite specificities in the blood of the immune cattle were carried out for 5 of the animals. The results in terms of parasite specificity of cytotoxic cells were very similar to those obtained with in vitro cytotoxicity assays. In summary, these experiments have revealed that the buffalo-derived parasite stocks Tp1(7014), (7013), (6999), (7065), (6998) and the cattle derived Ipp(Uganda) stock were able to induce generation of cytotoxic I-cells in vivo which are capable of recognizing parasite antigens on cells infected with many different T.parva parasite stocks although the proportion of cells killed was low for some of the cell lines. Further, lymphocytes from 1 steer which had cytolytic activity against a large number of infected cell lines were cloned in order to determine- if individual immune I-cells were recognizing antigenic epitope(s) common among cells infected with different stocks of I.parva, or if the broad specificity of killing was due to a heterologous mix of cytotoxic cells with varying antigen specificities. Two of the I cell cytotoxic clones generated gave greater than 50% cytotoxicity on all of the infected target cells at an effector to target ratio of less than 5:1. Such cloned cells will be very useful in future studies designed to identify the common or cross-reactive antigenic epitope and the parasite gene encoding for it, with a view towards constructing a recombinant vaccine against East coast fever.